Formulation and Evaluation of Cyclodextrin Inclusion Complex Tablets of Carvedilol - Arun Raj, R (Asian Journal of Pharmaceutics (AJP), 2016)
Objective: The aim of this series of experiments was to improve the solubility of a poorly soluble drug. Materials and Methods: Binary inclusion complexes of carvedilol and cyclodextrins derivatives were prepared by kneading method. Their solubility and dissolution behavior were compared with that of the pure drug and the marketed formulation of carvedilol. Results: Saturation solubility studies indicate that the solubility of the drug was increased and X-ray diffraction, differential scanning calorimetry, scanning electron microscopy showed that the crystalline nature of drug was lost or decreased significantly in the inclusion complex, indicating the drug was present in a solubilized form in the formulation. All inclusion complex tablets showed increase in dissolution rate than tablet prepared with pure drug. Formulation FT8 showed faster drug release in comparison to other formulations and data were fitted to various kinetic models. The mechanism of drug release from tablets was found to be Supercase 2 Transport. Stability studies suggested that there was no significant degradation or changes taking place in the tablets during the study period. Conclusion: It can be concluded that the inclusion complexation technique is an effective approach for the dissolution rate improvement of water insoluble drugs such as carvedilol.